Ocular myasthenia gravis saccades as a measure of extraocular muscle function - Wong, Sui H.; Bancroft, Matthew James; Tailor, Vijay K.; Abbas, Mohamed; Sekar, Akila; Noble, Claire; Theodorou, Maria; Kaski, Diego (Frontiers in Ophthalmology, 2022)
Background It is important to understand the pathophysiology of ocular myasthenia gravis (OMG) to improve treatment. Aim To use modern video-oculography to characterise saccadic eye movements in patients with OMG, including anti-AChR, anti-MuSK, anti-LRP4, and seronegative OMG. Methods In total, 21 patients with OMG and five age-matched healthy control subjects underwent video-oculography. Participants performed a sequence of horizontal saccades (3 minutes each) at ±5°, ± 10°, and ±20°, followed by 3 minutes of saccades directed at randomly presented targets at ±5°, ± 10°, and ±15°. We recorded the direction, amplitude, duration, peak, and average velocity of each saccade for each task for each participant. Results Saccadic amplitude, duration, and average velocity were all lower in OMG patients than in control subjects (p < 0.021). Saccadic amplitude and velocity decreased over time, but this decrease was similar in OMG patients and control subjects. Fixation drift and ocular disparity tended to be greater in OMG patients than in control subjects. Saccadic intrusions occurred more frequently in OMG patients than in control subjects (p < 0.001). No significant effects of time or group by time on fixation drift or ocular disparity were found. Discussion Saccadic velocities in OMG patients differed from those in normal control subjects, which suggests that OMG affects fast-twitch fibres, although fast-twitch fibres were still able to generate “twitch” or “quiver” movements in the presence of even severe ophthalmoplegia. Slow-twitch muscle fibres involved in gaze holding were also affected, accounting for increased fixation drift following saccades. Our objective finding of increased fixation drift and a larger number of saccadic intrusions mirror our anecdotal experience of patients with OMG who report significant diplopia despite minimal ophthalmoplegia on examination. Such microsaccades may be a surrogate for compensation of a gaze-holding deficit in MG.